2007
DOI: 10.1109/tuffc.2007.504
|View full text |Cite
|
Sign up to set email alerts
|

High Speed Imaging of Bubble Clouds Generated in Pulsed Ultrasound Cavitational Therapy - Histotripsy

Abstract: Our recent studies have demonstrated that mechanical fractionation of tissue structure with sharply demarcated boundaries can be achieved using short (<20 μs), high intensity ultrasound pulses delivered at low duty cycles. We have called this technique histotripsy. Histotripsy has potential clinical applications where noninvasive tissue fractionation and/or tissue removal are desired. The primary mechanism of histotripsy is thought to be acoustic cavitation, which is supported by a temporally changing acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(28 citation statements)
references
References 36 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…The pressure threshold for this simulation was defined as the pressure required to expand an initial bubble to >15 μm in radius, to be consistent with the minimum resolution for optical images recorded experimentally. This criteria is more reasonable for histotripsy therapy than the commonly used criteria for inertial cavitation of R max >2 R 0, since previous work has shown that histotripsy bubbles must be sufficiently expanded to sizes much greater than 2R 0 , often >50 μm, in order to fractionate tissue (Parsons et al 2006a; Xu et al 2007; Vlaisavljevich et al 2013a; Vlaisavljevich et al 2014c).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure threshold for this simulation was defined as the pressure required to expand an initial bubble to >15 μm in radius, to be consistent with the minimum resolution for optical images recorded experimentally. This criteria is more reasonable for histotripsy therapy than the commonly used criteria for inertial cavitation of R max >2 R 0, since previous work has shown that histotripsy bubbles must be sufficiently expanded to sizes much greater than 2R 0 , often >50 μm, in order to fractionate tissue (Parsons et al 2006a; Xu et al 2007; Vlaisavljevich et al 2013a; Vlaisavljevich et al 2014c).…”
Section: Methodsmentioning
confidence: 99%
“…Using the shock scattering mechanism, bubble clouds are initiated at negative pressures ranging from 10–28 MPa. Because of the complexity of the shock scattering process, multiple factors determine whether a cloud initiated, including the distribution of heterogeneous nuclei in the focal region, the size and shape of initial single bubbles, the number of cycles, the shock rise time, and the positive pressure amplitudes (Xu et al 2007; Maxwell et al 2010; Maxwell et al 2011b; Vlaisavljevich et al 2014b). Additionally, our previous study demonstrated that increases in tissue stiffness result in higher cloud initiation thresholds when using the shock scattering mechanism of bubble cloud formation (Vlaisavljevich et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Histotripsy depends on the initiation and maintenance of a cavitation bubble cloud to produce mechanical tissue fractionation (Parsons et al , 2006a; Xu et al , 2005). In order to effectively fractionate tissue into accelluar debris, histotripsy requires bubbles to rapidly expand from nanometer-sized initial nuclei into large cavitation bubbles greater than ~50μm in diameter (Parsons et al , 2006a; Vlaisavljevich et al , 2013a; Xu et al , 2007). Using a pressure high enough to initiate a bubble cloud and expand bubbles to a sufficient size, histotripsy has been shown capable of completely fractionating soft tissue into a liquid-appearing homogenate with no cellular structures remaining, resulting in effective tissue removal (Hall et al , 2007; Roberts et al , 2006; Vlaisavljevich et al , 2013b; Xu et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As the tissue is fractionated, the ultrasound appearance becomes progressively hypoechoic. 69 Previous studies demonstrating the safety and efficacy of transabdominal histotripsy of the prostate in an in vivo canine benign prostatic hypertrophy model 10 led us to hypothesize that prostate histotripsy could potentially have a role in the focal management of PCa.…”
mentioning
confidence: 99%